Foraging and metabolic consequences of semi-anadromy for an endangered estuarine fish. - Bruce G Hammock; Steven B Slater; Randall D Baxter; Nann A Fangue; Dennis Cocherell; April Hennessy; Tomofumi Kurobe; Christopher Y Tai; Swee J Teh (PLoS ONE, 2017)
Diadromy affords fish access to productive ecosystems, increasing growth and ultimately fitness, but it is unclear whether these advantages persist for species migrating within highly altered habitat. Here, we compared the foraging success of wild Delta Smelt-an endangered, zooplanktivorous, annual, semi-anadromous fish that is endemic to the highly altered San Francisco Estuary (SFE)-collected from freshwater (<0.55 psu) and brackish habitat (≥0.55 psu). Stomach fullness, averaged across three generations of wild Delta Smelt sampled from juvenile through adult life stages (n = 1,318), was 1.5-fold higher in brackish than in freshwater habitat. However, salinity and season interacted, with higher fullness (1.7-fold) in freshwater than in brackish habitat in summer, but far higher fullness in brackish than freshwater habitat during fall/winter and winter/spring (1.8 and 2.0-fold, respectively). To examine potential causes of this interaction we compared mesozooplankton abundance, collected concurrently with the Delta Smelt, in freshwater and brackish habitat during summer and fall/winter, and the metabolic rate of sub-adult Delta Smelt acclimated to salinities of 0.4, 2.0, and 12.0 psu in a laboratory experiment. A seasonal peak in mesozooplankton density coincided with the summer peak in Delta Smelt foraging success in freshwater, and a pronounced decline in freshwater mesozooplankton abundance in the fall coincided with declining stomach fullness, which persisted for the remainder of the year (fall, winter and spring). In brackish habitat, greater foraging 'efficiency' (prey items in stomachs/mesozooplankton abundance) led to more prey items per fish and generally higher stomach fullness (i.e., a higher proportion of mesozooplankton detected in concurrent trawls were eaten by fish in brackish habitat). Delta Smelt exhibited no difference in metabolic rate across the three salinities, indicating that metabolic responses to salinity are unlikely to have caused the stomach fullness results. Adult migration and freshwater spawning therefore places young fish in a position to exploit higher densities of prey in freshwater in the late spring/summer, and subsequent movement downstream provides older fish more accessible prey in brackish habitat. Thus, despite endemism to a highly-altered estuary, semi-anadromy provided substantial foraging benefits to Delta Smelt, consistent with other temperate migratory fish.